Mortality due to Respiratory Syncytial Virus. Burden and Risk Factors - Geoghegan, Sarah; Erviti, Anabella; Caballero, Mauricio T.; Vallone, Fernando; Zanone, Stella M.; Losada, Juan Ves; Bianchi, Alejandra; Acosta, Patricio L.; Talarico, Laura B.; Ferretti, Adrian; Grimaldi, Luciano Alva; Sancilio, Andrea; et al. (American journal of respiratory and critical care medicine, 2017)
Respiratory syncytial virus (RSV) is the most frequent cause of hospitalization and an important cause of death in infants in the developing world. The relative contribution of social, biologic, and clinical risk factors to RSV mortality in low-income regions is unclear. To determine the burden and risk factors for mortality due to RSV in a low-income population of 84,840 infants. This was a prospective, population-based, cross-sectional, multicenter study conducted between 2011 and 2013. Hospitalizations and deaths due to severe lower respiratory tract illness (LRTI) were recorded during the RSV season. All-cause hospital deaths and community deaths were monitored. Risk factors for respiratory failure (RF) and mortality due to RSV were assessed using a hierarchical, logistic regression model. A total of 2,588 (65.5%) infants with severe LRTI were infected with RSV. A total of 157 infants (148 postneonatal) experienced RF or died with RSV. RSV LRTI accounted for 57% fatal LRTI tested for the virus. A diagnosis of sepsis (odds ratio [OR], 17.03; 95% confidence interval [CI], 13.14-21.16 for RF) (OR, 119.39; 95% CI, 50.98-273.34 for death) and pneumothorax (OR, 17.15; 95% CI, 13.07-21.01 for RF) (OR, 65.49; 95% CI, 28.90-139.17 for death) were the main determinants of poor outcomes. RSV was the most frequent cause of mortality in low-income postneonatal infants. RF and death due to RSV LRTI, almost exclusively associated with prematurity and cardiopulmonary diseases in industrialized countries, primarily affect term infants in a developing world environment. Poor outcomes at hospitals are frequent and associated with the cooccurrence of bacterial sepsis and clinically significant pneumothoraxes.